TRANSURETHRAL RESECTION OF PROSTATE: EARLY VERSUS DELAYED REMOVAL OF CATHETER - Durrani, Saadia Nawaz; Khan, Sarhad; Rehman, Ata ur (Journal of Ayub Medical College Abbottabad, 2014)
Background: Transurethral resection of prostate is the gold standard operation for bladder outflow obstruction due to benign prostatic enlargement. However, catheter removal day is variable. The objective of this study was to compare early and delayed catheter removal groups in terms of length of hospital stay, weight of resected prostate, duration of resection, peri-operative blood transfusion, and postoperative complications. Methods: This randomized controlled trial was carried out in Urology Unit-B, Institute of Kidney Diseases Peshawar from 1st September 2009 to 31st July 2011. Patients were selected by simple random sampling technique after taking informed consent and divided into two groups: Group A-standard catheter removal group and Group B-early catheter removal group. The study excluded patients with large post-void urine volume, simultaneous internal urethrotomy and transurethral resection of prostate, co-morbidity and intra-operative complications. Patients were discharged after removal of catheter if they voided successfully. In Group-A the catheters were kept for more than one day according to the standard protocol of our ward. The data were analysed using SPSS-17. Results: The study included 320 patients, 163 in Group-A and 157 in Group-B. Mean weight of resected tissue in Group-A was 46.67±9.133 grams; it was 45.22±7.532 grams in group B. Mean catheter removal day was 4.13±1.65days in Group-A; and 1.23±0.933 days in Group-B. Mean length of hospital stay was 3.57 days±1.028 in Group-A and 1.29 days±1.030 in Group-B (p-value<0.05). Length of hospital stay strongly correlated with the day of catheter removal. There was no significant difference between the two groups in terms of postoperative complications. Conclusion: Removal of catheter on first postoperative day after transurethral prostatectomy does not increase the postoperative complications and results in shorter hospital stay. Keywords: Transurethral resection of prostate, urinary catheterization, postoperative complications